Vulnerability to climate warming of four genera of New World iguanians based on their thermal ecology - Piantoni, Carla (2016)
Climate change and rising global temperatures pose a serious threat to biodiversity. We assessed the vulnerability to global warming of four genera of iguanian lizards whose distributions include a broad range of environments from the Peninsula of Yucatán to southern Patagonia. Original data on body temperatures (Tb), operative temperatures (Te, ‘null temperatures’ for non-regulating animals), thermoregulatory set-point range (preferred body temperatures, Tset) and quantitative indices of temperature regulation and quality of the thermal environment (db, de and E) for Tropidurus species were compared to published data for Anolis, Liolaemus and Sceloporus. Our results suggest that thermoregulatory behavior typically increases with latitude and altitude (except for two southernmost liolaemids), and that tropical and lowland lizards generally behave as thermoconformers. In a warming scenario, thermoconformity or poor thermoregulation in environments where large proportions of Tb and Te exceed the population's Tset will cause a reduction in the hours of activity and a higher risk of overheating. These results identify tropical populations as the most vulnerable to rising temperatures, especially the ones inhabiting open and low elevation sites. This indicates that protection of these environments should be a conservation priority. In contrast, Patagonia and montane environments represent potential future thermal refuges for many equator-ward or lowland lizards that, if capable of dispersion, would eventually be forced to retreat to these environments.